The Relationship Between Parental Verbal Abuse Behavior and Psychosocial Development of School-Age Children - Fuadah, Dina Zakiyyatul; Ludyanti, Laviana Nita; Oktaviana, Nurul Adinda (Chakra Brahmanda Lentera Institute, 2023)
Background: One of the problem phenomena that still occurs in school-age children is verbal abuse, violence that harms children physically and verbally. Children who get verbal abuse will generally imitate the same things they receive from their parents. This research aimed to analyze the correlation between parental verbal abuse behavior and psychosocial development in school-age children. Method: This research used a correlational design with a cross-sectional approach. The research population was 40 school-age children (11-12 years) at MI Miftahul Huda Jatisari, with a sample of 36 respondents obtained from a purposive sampling technique. Data collection of independent variable Korean Verbal Abuse Questionnaire (K-VAQ) modification and dependent variables of children's psychosocial development used questionnaires. Results: almost (69.4%) received severe verbal abuse, and most (63.9%) had poor psychosocial development. The statistical test results used Spearman Rho obtained a p-value of 0.013 (p-value < α), then H1 was accepted with R = 0.408, which means the strength of the relations. The correlation coefficient was positive, including a direct correlation, meaning that the more severe verbal abuse parents increasingly lacked psychosocial development of children. Conclusion: Psychosocial development of children is influenced by factors from parents' behavior in educating children. Parents' mistakes in responding to mistakes by scolding/blaming children can cause children to feel ashamed and worthless. It is hoped that parents should not verbally abuse children because it will lead children to behavior that inhibits or harms the child themselves.